(untitled) - RAHAYU NINGSIH, TITIK (Jurnal Ilmu Manajemen (JIM), 2017)
The purpose of the study to analyze the effect of bid-ask spread, market value, and variance return on holding period of stock mining sector listed in Indonesia Stock Exchange (BEI) 2011-2015. The sampling technique used purposive sampling technique and according to the criterias can obtain 10 companies. Data analysis technique used is multiple linear regression analysis. The result of the study simultaneously all independent variables affect the stock holding period. The study partially indicates that bid-ask spread and market value affect significantly to stock holding period. While variance return didn’t affect the stock holding period. The effect of bid-ask spread can be caused investors prefer stock of giving bigger benefits that is reflected from spread and many investors didn’t like the presence of risk. The effect of market value can be caused by investors perseption of stock price risk and investor aimed to speculate only. Variance return did’nt affect on stock holding period can because the value of variance samples used is too low and didn’t vary (homogeneous) caused the low stock price fluctuation during the study period and the investors want profit from the devidend only. Keywords: stock holding period, bid-ask spread, market value, variance return